Ecological correlates of crop yield growth and interannual yield variation at a global scale - Gleiser, Gabriela Laura (2021)
Artificial selection and genetic engineering plus an expanding repertoire and use of agrochemical inputs have allowed a rapid and continuous increase in crop yield (i.e., volume production per unit area) over the last century, which is needed to fulfill food demands from a growing human population. However, the first signs of yield deceleration and stagnation have already been reported for some globally important crops. Therefore, the study of the drivers of yield growth and its variation is essential for directing research and policies aiming at ensuring food security in the forthcoming years. We used data on mean and variability in annual yield growth for 107 globally important crops to assess the role of environmental (i.e., climatic region) and plant intrinsic traits (i.e., type of harvested organ, pollinator dependence, and life form) as drivers of change in yield growth and its stability. We applied a comparative approach to control for biases associated with phylogenetic non-independence among crops, an approach rarely used in agronomic studies. Average yield growth and its variation were not phylogenetically structured. Yield growth decreased with increasing pollinator dependence in tree crops but not in herbaceous and shrubby crops. Interannual yield variation tended to increase with increasing pollinator dependence, and it was higher in crops from temperate regions, in those cultivated for their reproductive organs, and in tree and shrubby crops as compared with herbaceous ones. Information on ecological correlates of crop yield growth and interannual yield variation can be used in the design of more sustainable and diversified agriculture schemes.